2004
DOI: 10.1021/bi035683k
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Role of Helix Caps in Protein Folding Is Context-Dependent

Abstract: Secondary structure punctuation through specific backbone and side chain interactions at the beginning and end of R-helices has been proposed to play a key role in hierarchical protein folding mechanisms [Baldwin, R. L., and Rose, G. D. (1999) Trends Biochem. Sci. 24, 26-33;Presta, L. G., and Rose, G. D. (1988) Science 240, 1632-1641. We have made site-specific substitutions in the N-and C-cap motifs of the 5-helix protein monomeric λ repressor (λ 6-85 ) and have measured the rate constants for folding and unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
(115 reference statements)
0
18
0
Order By: Relevance
“…Several studies have shown that so-called N-and C-capping structural motifs can stabilize a-helices through hydrogen-bonding or hydrophobic interactions (41)(42)(43). Thr 164 at homeodomain position 41 is located in the N-cap position of the N-capping motif, which initiates the third helix of the homeodomain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have shown that so-called N-and C-capping structural motifs can stabilize a-helices through hydrogen-bonding or hydrophobic interactions (41)(42)(43). Thr 164 at homeodomain position 41 is located in the N-cap position of the N-capping motif, which initiates the third helix of the homeodomain.…”
Section: Resultsmentioning
confidence: 99%
“…Thr 41 is well conserved among other NK-like homeodomain sequences (35) and is located at the NH 2 -terminal cap position of the third helix in the NKX3.1 homeodomain. The NH 2 -terminal helix cap is important for maintenance of the helical structure and its alteration may affect helix formation (41,42). Although Thr 41 is not involved in direct hydrogen bonding with the NKX3.1 DNA recognition sequence, it is likely to affect helix III structure and both DNA and protein interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4). Whereas metal binding at site III is primarily responsible for stabilizing the hydrophobic core (12), helix-capping interactions are known to increase domain stability and accelerate folding (28). Destabilization of N-cap interactions in helices C and G by mutation have been shown to decrease Ca 2ϩ -binding affinity in TnC (15,27).…”
Section: Methodsmentioning
confidence: 99%